Analytical Assessment of Kelvin‐Helmholtz Instability Growth at Ganymede's Upstream Magnetopause. Issue 8 (20th August 2021) - Kaweeyanun, N.; Masters, A.; Jia, X.
Abstract: Ganymede is the only Solar System moon that generates a permanent magnetic field. Dynamics within the Ganymedean magnetosphere is thought to be driven by energy‐transfer interactions on its upstream magnetopause. Previously in Kaweeyanun et al. (2020), https://doi.org/10.1029/2019GL086228 we created a steady‐state analytical model of Ganymede's magnetopause and predicted global‐scale magnetic reconnection to occur frequently throughout the surface. This paper subsequently provides the first assessment of Kelvin‐Helmholtz (K‐H) instability growth on the magnetopause. Using the same analytical model, we find that linear K‐H waves are expected on both Ganymedean magnetopause flanks. Once formed, the waves propagate downstream at roughly half the speed of the external Jovian plasma flow. The Ganymedean K‐H instability growth is asymmetric between magnetopause flanks due to the finite Larmor radius effect arising from large gyroradii of Jovian plasma ions. A small but notable enhancement is expected on the sub‐Jovian flank according to the physical understanding of bulk plasma and local ion flows alongside comparisons to the well‐observed magnetopause of Mercury. Further evaluation shows that nonlinear K‐H vortices should be strongly suppressed by concurring global‐scale magnetic reconnection at Ganymede. Reconnection is therefore the dominant cross‐magnetopause energy‐transfer mechanism and driver of global‐scale plasma convection within Ganymede's magnetosphere. Plain Language Summary: Ganymede is the largest moon of Jupiter, and the only moon in the Solar System that can maintain a permanent magnetic field. Current research suggests Ganymede contains two internal magnetic field sources—a molten iron core and a subsurface ocean. The study of Ganymede's magnetic environment will be a primary objective for the JUpiter ICy moon Explorer (JUICE), the first moon‐orbiting satellite mission set to launch in 2022. Ganymede is surrounded by flows of plasma (energized gas) which are normally deflected away by the magnetic field along a boundary called the upstream magnetopause. However, the magnetic shield can be broken through interactions on the magnetopause such as Kelvin‐Helmholtz (K‐H) instability. Using a mathematical model established in Kaweeyanun et al. (2020), https://doi.org/10.1029/2019GL086228 we first determine that K‐H instability can grow as waves along Ganymede's magnetopause flank regions, and that the growth is enhanced on the magnetopause flank that is closest to Jupiter due to motions of local plasma. Finally, using Mercury as a comparison case, we argue that K‐H waves are unlikely to grow into turbulent vortices that can inject plasma across the magnetopause, as they will be torn apart by another magnetopause process known as magnetic reconnection. Key Points: We present the first assessment of Kelvin‐Helmholtz (K‐H) instability on Ganymede's upstream magnetopause using an analytical model Linear K‐H waves can grow on both magnetopause flanks with small enhancement on the sub‐Jovian flank due to the finite Larmor radius effect Nonlinear K‐H vortices should be suppressed by magnetic reconnection, so the latter likely dominates cross‐magnetopause plasma transport